+0  
 
0
54
1
avatar

Find the value of t such that (5x^2 - 6x + 7)(4x^2 +tx + 10) = 20x^4 -9x^3+ 60x^2 - 39x + 70.

 Aug 6, 2021
 #1
avatar+12231 
+1

Find the value of t such that (5x^2 - 6x + 7)(4x^2 +tx + 10) = 20x^4 -9x^3+ 60x^2 - 39x + 70.

 

Hello Guest!

 

\( (5x^2 - 6x + 7)(4x^2 +{\color{blue}tx} + 10) =20x^4 -9x^3+ 60x^2 - 39x + 70\)

 

\((20x^4 -9x^3+ 60x^2 - 39x + 70): (5x^2 - 6x + 7)\\ =4x^2 +{\color{blue}3x} + 10\)

\(t=3\)

laugh  !

 Aug 7, 2021
edited by asinus  Aug 7, 2021

36 Online Users

avatar
avatar
avatar